Analisis pola perkembangan Kota Lewoleba berdasarkan morfologi ruang Kota Lewoleba - Satria Mandala; Jumadil, Jumadil; Hasanuddin, Hasanuddin (Teknosains: Media Informasi Sains dan Teknologi, 2025)
Abstract : The aim of this research is to analyze the development pattern of Lewoleba City regarding the spatial morphology of Lewoleba City, Lembata Regency. This type of research is quantitative using a descriptive observational research design. The population in this study is the entire community in the Lewoleba City Government, totaling 36,426 people. Sampling was carried out using a simple random sampling method. personal. To determine the population, it ranges from 5% to 15% of the total population. Data were analyzed regarding the analysis of Lewoleba City Development Patterns on the Spatial Morphology of Lewoleba City, Lembata Regency, research through qualitative descriptive descriptions. Validity tests are carried out to check construct validity and content validity. Construct validity is carried out by the author with the opinion of experts (evaluation experience). After the data is tabulated, then construct validity testing is carried out using factor analysis, namely by correlating between instrument product scores using the product moment correlation formula. The data analysis technique used Descriptive Statistics is used for hypothesis testing purposes to determine and describe the sample characteristics of each variable studied in this research. The results of the analysis show that by analyzing the development pattern of Lewoleba City regarding the spatial morphology of Lewoleba City, Lembata Regency, it can provide benefits to the local government in planning Lewoleba City in the future with sustainable development policies. The significant factors that influence are Land Use, Population Growth, Infrastructure, Road Network, Accessibility and Geographical Conditions. Key words: City Development Pattern, Spatial Morphology, Lewoleba City